CONSUMER PREFERENCES FOR ARABICA COFFEE DRINKS AT MD COFFEE ROASTER & COFFEE STORE BENER MERIAH DISTRICT - Widya Ramadhani; Irada Sinta; Riani (LPPM Universitas Malikussaleh - Indonesia, 2025)
MD Coffee is a culinary specialty of Gayo arabica coffee. The name MD Coffee is taken from the abbreviation of his parents' name, Mr. Mudiono (abbreviated as MD). In 2017 MD Coffee was established, MD Coffee has a variety of coffee variants with unique and authentic flavors (bitter and sweet). MD Coffee has interesting things, namely coffee beverage products that are suitable for various groups of young people and parents, arabica coffee drinks with flavors (bitter and sweet), temperatures (hot and cold) that vary and coffee drinks with variants (americano, black coffee, espresso and double espresso) that are diverse are an attraction for MD Coffee. This study aims to determine consumer preferences for product attributes of arabica coffee drinks at MD Coffee. This research method uses a quantitative descriptive method using conjoin analysis. The results of this study indicate the NPR value of variants (54,660) the variants available at MD Coffee are americano, black coffee, espresso and double espresso, the NPR value of taste (24,311) the flavors available at MD Coffee are bitter and sweet, the NPR value of temperature (21,030) the temperatures available at MD Coffee are hot and cold. The combination of attributes that consumers prefer in arabica coffee beverage products at MD Coffee is the espresso variant, bitter taste, and hot temperature.. Keywords: Product attributes, Arabica Coffee, Consumer Preferences.